Molecular Dynamics Simulation Study of the Interaction between Human Angiotensin Converting Enzyme 2 and Spike Protein Receptor Binding Domain of the SARS-CoV-2 B.1.617 Variant - Priya Antony (Biomolecules, 2021)
The COVID-19 pandemic, caused by the SARS-CoV-2 virus, has had a significant impact on people’s daily lives. The rapidly spreading B.1.617 lineage harbors two key mutations—L452R and E484Q—in the receptor binding domain (RBD) of its spike (S) protein. To understand the impact and structural dynamics of the variations in the interface of S protein and its host factor, the human angiotensin-converting enzyme 2 (hACE2), triplicate 500 ns molecular dynamics simulations were performed using single (E484Q or L452R) and double (E484Q + L452R) mutant structures and compared to wild type simulations. Our results indicate that the E484Q mutation disrupts the conserved salt bridge formed between Lys31 of hACE2 and Glu484 of S protein. Additionally, E484Q, which could favor the up conformation of the RBD, may help in enhanced hACE2 binding and immune escape. L452R introduces a charged patch near the binding surface that permits increased electrostatic attraction between the proteins. An improved network of intramolecular interactions observed is likely to increase the stability of the S protein and conformational changes may prevent the binding of neutralizing antibodies. The results obtained from the molecular dynamics simulations suggest that structural and dynamic changes introduced by these variations enhance the affinity of the viral S protein to hACE2 and could form the basis for further studies.